PEMBERDAYAAN KELOMPOK TANI NGIRING DATU I MELALUI PENGELOLAAN TANAMAN TERPADU PADI BERPIGEMEN BERAS MERAH UNTUK PEMENUHAN PANGAN SEHAT - Aryana, I Gusti Putu Muliarta; Sudika, I Wayan; Sudhramawan, Anak Agung Ketut; Suliartini, Ni Wayan Sri; Haeruman, Haeruman (Jurnal Abdi Insani, 2025)
In order to maintain West Nusa Tenggara as one of the national food barns and participate in maintaining rice self-sufficiency and knowing healthy food, it is necessary to introduce new innovations in the correct Integrated Crop Management technology through training and demonstration plots of red rice pigmented rice. The problem encountered in the Ngiring Datu I farmer group in Pringgejurang Utara Village, Montong Gading District, East Lombok is that they have not yet implemented the Integrated Crop Management and healthy red rice food comprehensively. The purpose of this activity is to increase the understanding, attitudes and skills of partner group members related to the implementation of Integrated Crop Management, especially in the use of new superior varieties of red rice pigmented rice Inapago Unram 1, the use of quality seeds and plant population management through 4:1 legowo planting, and it is hoped that there will be an increase in knowledge about the benefits of red rice for health. The method used in this program is a training method followed by practical work in the field and participatory action research in the field from preparation to evaluation by involving students of the Community Service Program (KKN). The activity stages include 1 day of training and field laboratory practice (Demplot) of planting rice with red rice pigment of superior variety Inpago Unram I using quality seeds through a 4:1 legowo row planting system, 18 days old seedlings on an irrigated rice field area of ​​10 are for 3.5 months starting from January - April 2025. Evaluation to measure the success of this activity is carried out through participant responses during the delivery of theory/training, participant responses during the implementation of field practice, mentoring and observations in the field laboratory plot. The results of the activity show that the extension participants consisting of village heads, heads of farmer groups or their representatives, youth leaders of Pringgejurang Utara village, Montong Gading sub-district, East Lombok Regency, have understood the description of the superior variety of red rice pigmented rice Inpago Unram 1, its content and benefits for health, and understand the Cultivation Technology of red rice pigmented rice Inpago Unram 1 through Integrated Crop Management, especially using 18-day seedling age and with the Jajar Legowo 4:1 planting pattern. Through the Integrated Crop Management Demonstration activity of red rice pigmented rice Inpago Unram 1 in the "Ngiring Datu I" Farmer Group, skills in cultivating superior rice varieties Inpago Unram1 have been improved using 18-day seedling age, as well as the Jajar Legewo 4:1 planting pattern with a harvest of 5.5 tons/ha of dry milled grain.